STRATEGI PENGUATAN MORAL SISWA MI/SD - Astuti, Aprilia Aisyah; Heraningtyas, Nur Luthfi Rizqa (Jurnal Inovasi dan Teknologi Pendidikan, 2023)
Education is very important to strengthen moral values in MI / SD students. This moral must be taught to MI/SD students through several strategies. This article aims to describe the Moral Strengthening Strategy for MI/SD students. This research employs a qualitative approach in conducting a literature review. The information utilized in this investigation relies on secondary sources, specifically research findings from relevant journals related to the chosen topic. Morality encompasses a collection of principles concerning individuals and their behaviors. It is characterized as the guidance on what is considered right or wrong, which is widely acknowledged in terms of actions and attitudes, morals, manners, and morals. An immoral person is a person who has no morals, therefore moral education is a solution to realize human beings who are virtuous, ethical, and have noble character so that they can become more responsible individuals who can live well in society. Some strategies that can be done to strengthen the morale of MI/SD students are by providing knowledge, and prioritizing morals, character, attitudes, ethics and behavior